PENINGKATAN PERAN SERTA PEREMPUAN DALAM UPAYA PERBAIKAN EKONOMI KELUARGA - Seminari, N.K.; Purnawati, N.K.; Artini, L.G.S.; Tara L.D., I.G.A. (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
Most women in Bali think that their people receive different treatment. Women in Bali are required to master many things related to ritual processions, customs and culture. However, it cannot be denied that currently women also have a role in helping the family economy. The dual roles carried out by women have hampered the development of their abilities and skills. Seeing this phenomenon, it is necessary to empower the community, especially women's empowerment. Based on this, service was carried out with the title Increasing the Role of Women in Efforts to Improve the Family Economy in Gulingan Village, Mengwi District, Badung Regency. The aim of service is to increase the role of women in efforts to improve the family economy. The service participants were women from PKK Banjar Munggu, Gulingan Village. The number of participants was 39 people. The results of service are being able to increase knowledge and develop the abilities of women, trying to fill every free time with activities that provide economic value, and participating in village development. Keywords: The role of women, efforts to improve, family economics